COMBATING DENGUE: EXPERIENCE OF THE PATIENT SAFETY LEAGUE (LASPAC) (CIPEEX, 2025)
Introduction: Dengue is an infectious disease transmitted by the Aedes aegypti mosquito, with no specific treatment available to date, making vaccination a crucial measure for its prevention. In Anápolis-Goiás, the Project UniEVANGÉLICA Itinerant Citizen -- ImmunizACTION Health Education was developed to increase vaccination coverage and raise population awareness about the importance of vaccination. Objective: To raise children's awareness about dengue prevention and the importance of vaccination, while providing nursing students with an opportunity to apply practical knowledge and develop communication skills. Methodology: The activity was carried out at an elementary school in Anápolis, involving approximately 90 children aged 3 to 10 years. Interactive lectures and playful activities, such as games and simulations, were organized and adapted to facilitate understanding for the child audience. Results: The activities proved to be effective, with children actively participating and demonstrating good assimilation of the content. The playful and interactive methodology contributed to engagement and learning, and the experience was enriching for both the children and the students, who improved their communication skills. Conclusion: The educational activity provided students with a significant practical experience, contributing to their personal and professional growth. Socially, it is expected that the awareness generated among children will expand to their families, promoting greater adherence to dengue prevention and control practices in the community.
Keywords: Experience report; Dengue; Vaccination; Health promotion